DEVELOPMENT OF CRITERIA FOR EVALUATION OF THE FORMATION OF PROFESSIONALLY SIGNIFICANT LEADERSHIP QUALITIES AMONG STUDENTS OF PEDAGOGICAL COLLEGE - N. V. Kubarkova (Образование и наука)
The aim of the article is to give a theoretical justification of the criteria, indicators and measuring instruments for diagnostics of professionally significant leadership qualities of a teacher.Methods. Research material is presented from positions of the system and activity approaches. The first one allowed to develop the structure of professionally significant leadership qualities of a teacher, which includes twelve individual abilities and traits. The second one, abilities and individual features, their manifestation and development are considered from the standpoint of systemogenesis of professional activity. From these positions defined criteria basis for the diagnosis of professionally significant leadership qualities of a teacher. Methods of content analysis and content-logical intersections are used while defining the concept of «professionally significant leadership qualities of a teacher» and elaboration of its component composition. The method of concept analysis is used to determine criteria and indicators for diagnostics of professionally significant leadership qualities of a teacher.Results. The criteria and indicators, diagnostic tools for the detection of the formation of professionally significant leadership qualities of students of pedagogical college; the characteristic of used methods are given. Scientific novelty. The article provides a definition of the concept «professionally significant qualities of leadership of the teacher» is defined by the author; essence of such qualities is revealed.Practical significance. Described in this article approaches to definition of criteria and indicators may be of interest to researchers, graduate students, undergraduates. Listed diagnostic tools can be used in the performance appraisal of teachers for evaluating their leadership qualities.